Crude Oil Theft in the Niger Delta: The Oil Companies and Host Communities Conundrum - Collins ,H. Wizor; Elekwachi, Wali (International Journal of Research and Scientific Innovation (IJRSI, 2020)
This study investigated crude oil theft in the Niger Delta, the oil companies and host communities’ dilemma using the Bayelsa state swamp area operated by Nigerian Agip Oil Company (NAOC) as a case study. The roles and functions of the oil companies and their host communities towards crude oil theft in the Niger Delta was examined to determine the rate of crude oil theft during the resurgence of pockets of militancy, after the declaration of amnesty by the Nigerian government and the period of full implementation of the amnesty programme in the Niger Delta. Secondary data from the National Oil Spill Detection and Response Agency (NOSDRA) and NAOC Swamp area operation in Bayelsa State was used to determine the rate of crude oil theft during these periods in the Niger Delta. The total number of incidences of crude oil spill each year starting from 2010 to 2014 were calculated using statistical tools in determining the average spills per month, and the percentage of spills each year. Chi-square statistical technique was used to complete and analyze the research hypotheses. The results indicate that oil spills through equipment failure, operational errors and corrosion were generally few. Surprisingly, those caused by crude oil theft (sabotage) during the resurgence of pockets of militancy was low when compared with post militancy or amnesty implementation period. The study further reveals that from the later part of 2011 to 2014, the number of spills became constantly high, indicating that amnesty only bridged the gap between the security agencies and other government bodies fighting against oil theft and militants, to join forces in the cause of crude oil theft. Also, the study shows that between 2010 to 2014, sabotage accounted for 1,379 spills out of a total of 1,640 spills. Crude oil theft through sabotage as at 2010 was 5.2%; it rose to 37.4% in 2014 suggesting that five years after the full amnesty implementation, the problem of crude oil theft remained unsolved in the Niger Delta. The study, therefore, recommends among others, an improved developmental plan of the Niger Delta by government and the International Oil Companies (OICs), involvement of the host communities in the management and security of oil installations in their catchment areas, Realtime monitoring of the security men and the criminals, using satellite systems, CCTV and other digital instruments and expansion of corporate social responsibility (CSR) by the oil companies.
Keywords: Crude oil; Host communities; Multinational oil companies; Niger Delta; Nigeria; Sabotage; Spills; Theft